Pharmacoeconomics guidelines: The need of hour for India - Oberoi, Sukhvinder Singh; Oberoi, Avneet (International Journal of Pharmaceutical Investigation)
Although the government pays for approximately 20% of drugs used in India, private out-of-pocket expenditure in India on health-care is one of the highest in the world. Preparing pharmacoeconomics guidelines will be an important step in order to establish Health Technology Assessment (HTA) in India. Areas in which HTA could be applied in the Indian context include, drug pricing, development of clinical practice guidelines and prioritizing interventions that represent the greatest value within a limited budget. All this calls for action, both by government and civil-society organizations, to make access to essential medicines a priority.
Keywords: Drug pricing; essential medicines; health technology assessment; pharmacoeconomics